S DIFFUSIVITY IN FE-NI-S-P MELTS - Majewski E.; Walker D. (My University, 1998)
Soret diffusion rise times were observed and resolved for Fe-Ni-S-P melts at 10 kbar in thermal gradients between 1300 and 1450°C. A steady-state separation of S-rich components to the hot end of the ~2 mm long liquid charges is achieved in about 20 minutes. Chemical diffusivities of about 10-5 cm2/s are consistent with these observations and those of the compaction velocity of aggregates of crystalline Fe metal against the cold end of our experiments. These rapid diffusivities are not rapid enough for diffusion to be an important agent of bulk mass transfer in the addition or extraction of light elements in the Earth's core.
Keywords: THERMAL DIFFUSIVITY; SULFUR; CORE; MELTS